2015
DOI: 10.4103/2152-7806.156556
|View full text |Cite
|
Sign up to set email alerts
|

C5 Nerve root palsies following cervical spine surgery: A review

Abstract: Background:Cervical C5 nerve root palsies may occur in between 0% and 30% of routine anterior or posterior cervical spine operations. They are largely attributed to traction injuries/increased cord migration following anterior/posterior decompressions. Of interest, almost all studies cite spontaneous resolution of these deficits without surgery with 3–24 postoperative months.Methods:Different studies cite various frequencies for C5 root palsies following anterior or posterior cervical spine surgery. In their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…However, in all cases from the present series, the symptom of C5 palsy and the timing of the onset were typical, i.e., impairment of deltoid and biceps occurred several days after surgery without any sensory disturbance and severe girdle pain, as the previous authors had reported. Moreover, our results showed that all cases exhibited recovery from muscle weakness either fully or partially during the follow-up period, and that was also compatible with the recent review article [25]. Therefore, we would say that the possibility of contamination by other neurological pathologies such as motor neuron diseases and Parsonnage-Turner syndrome would be quite low in this series.…”
Section: Discussionsupporting
confidence: 93%
“…However, in all cases from the present series, the symptom of C5 palsy and the timing of the onset were typical, i.e., impairment of deltoid and biceps occurred several days after surgery without any sensory disturbance and severe girdle pain, as the previous authors had reported. Moreover, our results showed that all cases exhibited recovery from muscle weakness either fully or partially during the follow-up period, and that was also compatible with the recent review article [25]. Therefore, we would say that the possibility of contamination by other neurological pathologies such as motor neuron diseases and Parsonnage-Turner syndrome would be quite low in this series.…”
Section: Discussionsupporting
confidence: 93%
“…We found an incidence of 6% in C5 palsy, which was also within the previously reported range of 0%-30% [22][23][24][25]. No correlation was found between occurrence of C5 palsy and positive IONM signal alerts (p=0.73).…”
Section: Discussionsupporting
confidence: 88%
“…In the evaluation presented herein, nerve root injuries were the most frequent postoperative neurological deficits. A study reported that the incidence of C5 root deficits for the anterior and posterior approach in decompression at C4–C5 level was 12% [9]. C5 palsy was commonly caused by iatrogenic injury, reperfusion injury of the spinal cord, or impingement by an osteophyte with a tethering effect.…”
Section: Discussionmentioning
confidence: 99%